Usage of TV Studio Technology in the Production of Contest Programs (Herald of Journalism, 2019)
This research is concerned with comparing the usage of TV studio technology in the production of contest programs in official and private Sudanese TV channels at different times, to reach accurate findings. This research is classified under the umbrella of the descriptive studies, by applying content analysis as it is an accurate tool, depending on answering the questions of the study besides denying or proving research hypotheses.  The most important findings of this study are the private sector TV channels, depends on TV studio technology in the contesters program production, whereas, the official channels did not depend on it as modern technology was not common thirty years ago. The private sector TV channel relies on sponsoring companies in providing kind and cash prizes for the contesters of the competition programmes. The most necessary recommendations of this study are the importance of applying modern technol-ogy of the TV studio in producing high quality programmess, particularly, that programs which require attraction of viewers inside and outside the studio, the necessity of reducing the number of the TV production crew, in the case of applying the virtual TV studio, because, this type of the studio depends on the computer programmes in the production stages and offering Sudanese official TV channel more concern with supplying it with modern equipment to keep pace with technical development, which contributes to the best television production.
Keywords: Sudanese TV channels, TV studio technology, the production of contest programs.